Asuransi dan Pandemi Covid-19: Peran Persepsi Konsumen dalam Keputusan Pembelian - Ellen Cenora; Daniel Hermawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Consumer perception is a view or thought process used to make decisions in buying products or services that will be consumed. One of them is in purchase of insurance. This study aims to determine the influence of consumer perception on insurance purchase decisions at PT. Prudential Life Assurance during the Covid-19 pandemic in Bandung. This consumer perception is divided into 6 dimensions consisting of store image, product quality, price, promotion, service quality, and value. This research method uses quantitative. The population in this study are all Prudential customers who live in Bandung. The sampling technique used is non-probability sampling with purposive sampling type with a sample size of 100 people. Data was collected by means of a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of the study showed that consumer perception had a positive and significant effect on purchase decision. The dimension of service quality has a significant effect on purchase decision, while the dimensions of store image, product quality, price, promotion, and value have no significant effect on purchase decision. The dimension of service quality is the dimension of the consumer perception variable which dominantly influences purchase decision